Alkylation of Benz[a]anthracene Affects Toxicity to Early–Life Stage Zebrafish and In Vitro Aryl Hydrocarbon Receptor 2 Transactivation in a Position‐Dependent Manner. (25th June 2022) - Dubiel, Justin; Green, Derek; Raza, Yamin; Johnson, Hunter M.; Xia, Zhe; Tomy, Gregg T.; Hontela, Alice; Doering, Jon A.; Wiseman, Steve
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are structurally diverse organic chemicals that can have adverse effects on the health of fishes through activation of aryl hydrocarbon receptor 2 (AhR2). They are ubiquitous in the environment, but alkyl PAHs are more abundant in some environmental matrices. However, relatively little is known regarding the effects of alkylation on the toxicity of PAHs to fishes in vivo and how this relates to potency for activation of AhR2 in vitro. Therefore, the objectives of the present study were to determine the toxicity of benz[ a ]anthracene and three alkylated homologs representing various alkylation positions to early life stages of zebrafish ( Danio rerio ) and to assess the potency of each for activation of the zebrafish AhR2 in a standardized in vitro AhR transactivation assay. Exposure of embryos to each of the PAHs caused a dose‐dependent increase in mortality and malformations characteristic of AhR2 activation. Each alkyl homolog had in vivo toxicities and in vitro AhR2 activation potencies different from those of the parent PAH in a position‐dependent manner. However, there was no statistically significant linear relationship between responses measured in these assays. The results suggest a need for further investigation into the effect of alkylation on the toxicity of PAHs to fishes and greater consideration of the contribution of alkylated homologs in ecological risk assessments. Environ Toxicol Chem 2022;41:1993–2002. © 2022 SETAC Abstract : Alkylation alters the potency of benz[ a ]anthracene in vitro and in vivo. BAA = benz[ a ]anthracene; 8‐MBAA = 8‐methylbenz[ a ]anthracene; 4‐MBAA = 4‐methylbenz[ a ]anthracene; 7, 12‐DMBAA = 7, 12‐dimethylbenz[ a ]anthracene.